The Oxygen Consumption and Metabolic Cost of Walking and Running in Adults With Achondroplasia - Sims, David T.; Onambélé-Pearson, Gladys L.; Burden, Adrian; Payton, Carl; Morse, Christopher I. (Frontiers in Physiology, 2018)
The disproportionate body mass and leg length of Achondroplasic individuals may affect their net oxygen consumption (V͘O2) and metabolic cost (C) when walking at running compared to those of average stature (controls). The aim of this study was to measure submaximal V͘O2 and C during a range of set walking speeds (SWS; 0.56 – 1.94 m⋅s-1, increment 0.28 m⋅s-1), set running speeds (SRS; 1.67 – 3.33 m⋅s-1, increment 0.28 m⋅s-1) and a self-selected walking speed (SSW). V͘O2 and C was scaled to total body mass (TBM) and fat free mass (FFM) while gait speed was scaled to leg length using Froude’s number (Fr). Achondroplasic V͘O2TBM and V͘O2FFM were on average 29 and 35% greater during SWS (P < 0.05) and 12 and 18% higher during SRS (P < 0.05) than controls, respectively. Achondroplasic CTBM and CFFM were 29 and 33% greater during SWS (P < 0.05) and 12 and 18% greater during SRS (P < 0.05) than controls, respectively. There was no difference in SSW V͘O2TBM or V͘O2FFM between groups (P > 0.05), but CTBM and CFFM at SSW were 23 and 29% higher (P < 0.05) in the Achondroplasic group compared to controls, respectively. V͘O2TBM and V͘O2FFM correlated with Fr for both groups (r = 0.984 – 0.999, P < 0.05). Leg length accounted for the majority of the higher V͘O2TBM and V͘O2FFM in the Achondroplasic group, but further work is required to explain the higher Achondroplasic CTBM and CFFM at all speeds compared to controls. New and Noteworthy: There is a leftward shift of oxygen consumption scaled to total body mass and fat free mass in Achondroplasic adults when walking and running. This is nullified when talking into account leg length. However, despite these scalars, Achondroplasic individuals have a higher walking and metabolic cost compared to age matched non-Achondroplasic individuals, suggesting biomechanical differences between the groups.